Comprehensive Approach to Medical Nutrition Therapy in Patients with Type 2 Diabetes Mellitus: From Diet to Bioactive Compounds - Luigi Barrea; Claudia Vetrani; Ludovica Verde; Evelyn Frias-Toral; Florencia Ceriani; Simona Cernea; Annamaria Docimo; Chiara Graziadio; Devjit Tripathy; Silvia Savastano; Annamaria Colao; Giovanna Muscogiuri (MDPI AG, 2023)
In the pathogenesis of type 2 diabetes mellitus (T2DM), diet plays a key role. Individualized medical nutritional therapy, as part of lifestyle optimization, is one of the cornerstones for the management of T2DM and has been shown to improve metabolic outcomes. This paper discusses major aspects of the nutritional intervention (including macro- and micronutrients, nutraceuticals, and supplements), with key practical advice. Various eating patterns, such as the Mediterranean-style, low-carbohydrate, vegetarian or plant-based diets, as well as healthy eating plans with caloric deficits have been proven to have beneficial effects for patients with T2DM. So far, the evidence does not support a specific macronutrient distribution and meal plans should be individualized. Reducing the overall carbohydrate intake and replacing high glycemic index (GI) foods with low GI foods have been shown as valid options for patients with T2DM to improve glycemic control. Additionally, evidence supports the current recommendation to reduce the intake of free sugars to less than 10% of total energy intake, since their excessive intake promotes weight gain. The quality of fats seems to be rather important and the substitution of saturated and trans fatty acids with foods rich in monounsaturated and polyunsaturated fats lowers cardiovascular risk and improves glucose metabolism. There is no benefit of supplementation with antioxidants, such as carotene, vitamins E and C, or other micronutrients, due to the lack of consistent evidence showing efficacy and long-term safety. Some studies suggest possible beneficial metabolic effects of nutraceuticals in patients with T2DM, but more evidence about their efficacy and safety is still needed.